TI_GERICHTE 11.2007.156 vom 10. Juli 2009 , Assistenza giudiziaria: indigenza del richiedente proprietario di immobili? - TI Tribunale d'appello (2009)
Assistenza giudiziaria: indigenza del richiedente proprietario di immobili?